Enzym Methods in Wine Analysis - Kállay, M.; Bárdi, Gy.; Korány, K. (International Journal of Horticultural Science, 2001)
In our laboratory for special determinations BOERINGER-MANNHEIM’s enzyme-test combinations have been used for 10 years. Our present work deals with the practical aspects of the enzymatic determination of so important wine components like L-malic, L-lactic and citric acid, glycerol, D-gluconic acid, D-sorbitol, acetic aldehyde and D-glucose to D-fructose (G/F) ratio. Whenever possible, the results arc compared to the results of other methods (spectrophotometry, gas chromatography, polarimetry) used at our department.